Analisa Perbandingan Algoritma Goldbach dan LZW pada File WAV - Irawan, Muhammad Bima Arya; Pristiwanto, Pristiwanto (LPPM UNIKA Santo Thomas Medan, 2024)
WAV stands for Waveform Audio Format, an audio file standard developed by Microsoft and IBM. It is a variant of the RIFF bitstream format, similar to the IFF and AIFF formats used on Amiga and Macintosh systems. Both WAV and AIFF are compatible with Windows and Macintosh platforms. Although WAV files can contain compressed audio, they are typically used for uncompressed audio. The WAV format is part of Microsoft's RIFF specification for multimedia file storage. Compression is the process of reducing file size without significantly compromising data quality. The effectiveness of compression is eval_uated based on factors such as compression time, memory usage, output quality, and the final file format. This research suggests that compressing audio files can help optimize hard disk space. Various compression algorithms are available, and reducing audio file size can enhance storage efficiency.